Severe Neonatal Holocarboxylase Synthetase Deficiency in West African Siblings - De Castro, Mauricio (JIMD Rep, 2015)
In multiple carboxylase deficiency (MCD), the biotin-dependent carboxylases have decreased activity due to either biotinidase deficiency or holocarboxylase synthetase (HS) deficiency. We report the case of two siblings from Ghana, the first of which presented shortly after birth with profound lactic acidosis and a urine organic acid profile consistent with MCD. In the first sibling, treatment with pulverized biotin tablets (20 mg) was begun immediately, but the patient died at 10 days of age from cardiac arrest secondary to refractory metabolic acidosis. Autopsy revealed a biotin bezoar. Sequencing of HCLS showed homozygosity for a novel missense variant (p.G241W). The second sibling had a similar presentation at birth: severe metabolic acidosis and respiratory distress. A urine organic acid profile was consistent with HS deficiency; he was treated with biotin powder (20 mg), and after 24 h, the lactate decreased significantly; by day 5 of life, the patient was tolerating 40 mg of biotin, feeding by mouth and off all other medications and support. This is the first report of the p.G241W mutation. To our knowledge, this is also the first mutation described in West African patients with HS deficiency and the cases demonstrate that it is biotin responsive. Additionally, our experience suggests that the powdered form of biotin supplementation may be more digestible than tablets for the treatment of severe neonatal HS deficiency.